BOBOT BADAN SAPI PERANAKAN ONGOLE (PO) JANTAN DENGAN BEBERAPA METODE PENGUKURAN DI PASAR HEWAN PETAMBAKAN KABUPATEN BANJARNEGARA - Rudi Salam; Sulistyaningtyas; Fany Dwi Evadewi; Sari Eko Tuswati; Hasan Haren (MEDIA PETERNAKAN, 2024)
Research with the title "Body Weight of Male Ongole Crossbreed (PO) Cattle Using Several Measurement Methods at the Farm Animal Market, Banjarnegara Regency" was carried out on September 12, 2023. The aim of this research was to test the accuracy of the school and winter formulas compared with the weight of digital scales. The research was carried out using a survey method; the material used was 35 male Ongole crossbreed cattle aged ± 2 years. The parameters observed include body weight, chest circumference, and body length. Data analysis was carried out using the z test. The results of the research show that the calculated Z value between the Schoorl formula and digital scales is greater than the T table value (t0.05), namely (z = 2.05 > t0.05 = 1.65). This shows that there is a significant difference between the results of Schoorl's formula calculation of body weight on scales. The calculated Z value between the Winter formula and digital scales is greater than the T table value (t0.01), namely (z= 3.86 > t0.01 = 2.58). This shows that there is a very significant difference between the calculation results of the Winter formula and body weight on the scale. Of the two formulas, the most effective one used to estimate the body weight of Ongole crossbreed cattle (PO) is the Winter formula compared to the Schoorl formula.